Realism and Institutionalism in International Studies. - Brecher, Michael; Harvey, Frank P. (University of Michigan Press, 2009)
Realism and Institutionalism in International Studies represents a unique collection of original essays by foremost scholars in the field of International Studies. Six essays advocate, critique, or revise Realism, the theoretical paradigm that explains international politics by emphasizing security competition and war among states. The remaining four essays address Institutionalism, the paradigm that offers explanations for the formation, maintenance, variation, and significance of international institutions. The authors reflect on the strengths and weaknesses of these approaches and suggest research agendas for the future. Together, this volume provides an accessible and wide-ranging survey of the issues concerning two major paradigms in International Studies. This volume will be of interest to scholars and students alike and will undoubtedly determine the shape of future research. See table of contents and excerpts. Frank P. Harvey is Professor of Political Science and Director of the Centre for Foreign Policy Studies at Dalhousie University. Michael Brecher is the R.B. Angus Professor of Political Science at McGill University and past president of the International Studies Association. Millennial Reflections on International Studies This volume is part of the Millennial Reflections on International Studies project in which forty-five prominent scholars engage in self-critical, state-of-the-art reflection on international studies to stimulate debates about successes and failures and to address the larger questions of progress in the discipline. Other paperbacks from this project: Conflict, Security, Foreign Policy, and International Political Economy: Past Paths and Future Directions in International Studies Evaluating Methodology Critical Perspectives in International Studies The full collection of essays is available in the handbook Millennial Reflections on International Studies.